FEMINISME DAN PENDIDIKAN AGAMA ISLAM: STUDI KRITIS TERHADAP INTERPRETASI KITAB KLASIK - Uun Kurnaesih; Tati Dahliah; Fadhila Nurfalah Setia (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2025)
This study explores the intersection of feminism and Islamic religious education by critically a nalyzing interpretations of classical Islamic texts. Feminism, as a socio-political movement advocating for gender equality, often contrasts with traditional Islamic perspectives that emphasize distinct roles and responsibilities for men and women. This research examines the diverse interpretations of religious texts, cultural traditions, and societal norms that influence gender perceptions in Islamic contexts. Through a systematic literature review, the study identifies key areas of conflict and convergence between feminist thought and Islamic teachings, particularly regarding justice, rights, and the role of women in society. The findings highlight the potential for reinterpretation of religious texts to address gender bias while preserving Islamic principles. This research also critiques Western feminist ideologies that may conflict with Islamic values and proposes